2003
DOI: 10.2165/00007256-200333010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endurance Exercise on Autonomic Control of Heart Rate

Abstract: Long-term endurance training significantly influences how the autonomic nervous system controls heart function. Endurance training increases parasympathetic activity and decreases sympathetic activity in the human heart at rest. These two training-induced autonomic effects, coupled with a possible reduction in intrinsic heart rate, decrease resting heart rate. Long-term endurance training also decreases submaximal exercise heart rate by reducing sympathetic activity to the heart. Physiological ageing is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
281
7
19

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(343 citation statements)
references
References 123 publications
28
281
7
19
Order By: Relevance
“…18,19 Physical exercise may promote adjustments in cardiovascular control sites, such as the hypothalamus, solitary tract nucleus and the rostral ventrolateral medulla. These adaptations may occur via neural remodeling or endogenous factors, such as nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Physical exercise may promote adjustments in cardiovascular control sites, such as the hypothalamus, solitary tract nucleus and the rostral ventrolateral medulla. These adaptations may occur via neural remodeling or endogenous factors, such as nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…18 The benefits of aerobic physical training on cardiac autonomic control have been well documented in experimental and clinical studies. [19][20][21] Regular physical exercise promotes a tonic decrease in sympathetic autonomic control and an increase in vagal control. 22,23 However, the effects of physical exercise and ACEis, alone or in combination, on heart-rate variability and the capacity for autonomic balance rearrangement (for example, during the tilt test) have not been investigated in hypertensive (HT) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Female gender seems to result in a lower total variability (Vandeput et al 2012), whereas vagal modulation has been found to be similar (Moodithaya & Avadhany, 2012) or higher (Fukusaki et al 2000;Huikuri et al 1996) when compared to men. These differences in HRV are probably caused by lower sympathetic and higher vagal control of the heart in women (Carter et al 2003).…”
Section: Factors Affecting Hrvmentioning
confidence: 96%
“…Non-functional overreaching or overtraining syndrome has usually been found to decrease resting HRV (Uusitalo et al 1996;Baumert et al 2006;Hynynen et al 2007;Pichot et al 2000). Studies that have reported increase in VO2max of more than 12 ml/kg/min after endurance training have also reported an increase in vagal control of the heart (Carter et al 2003). Several studies have investigated the effects of training on nocturnal HRV, as sleep is an important period for both physiological and psychological recovery, and also offers reproducible, "controlled" measurement period for HRV, especially of high frequency power.…”
Section: Hrv and Endurance Trainingmentioning
confidence: 99%
“…Indeed, significant improvements in indices of autonomic cardiac modulation derived from the analysis of HRV (reflecting increases in cardiac vagal modulation) have been reported after the achievement of BP control with antihypertensive treatment 13,14 and in response to non-pharmacological interventions such as regular physical training. [15][16][17] Thus, the analysis of HRV appears to represent a simple means to assess autonomic cardiac modulation and a valuable tool to track the autonomic adjustments in the CV system, induced by a number of pharmacological and non-pharmacological interventions, although its specificity should not be taken for granted. 9 Further information on the clinical applicability of HRV analysis in the assessment of the effects of physical exercise is provided by the paper by Cozza et al 18 published in the current issue of Hypertension Research.…”
mentioning
confidence: 99%